Preparative Isolation and Purification of Three Sesquiterpenoid Lactones from Eupatorium lindleyanum DC. by High-Speed Counter-Current Chromatography - Yan, Guilong (Molecules, 2012)
A high-speed counter-current chromatography (HSCCC) method was established for the preparative separation of three sesquiterpenoid lactones from Eupatorium lindleyanum DC. The two-phase solvent system composed of n-hexane–ethyl acetate–methanol–water (1:4:2:3, v/v/v/v) was selected. From 540 mg of the n-butanol fraction of Eupatorium lindleyanum DC., 10.8 mg of 3β-hydroxy-8β-[4'-hydroxy-tigloyloxy]-costunolide, 17.9 mg of eupalinolide A and 19.3 mg of eupalinolide B were obtained in a one-step HSCCC separation, with purities of 91.8%, 97.9% and 97.1%, respectively, as determined by HPLC. Their structures were further identified by ESI-MS and (1)H-NMR.